Seismic Background Noise Level and Station Detectability in the Flores Sea - Khusnani, Azmi; Jufriansah, Adi; Anggraini, Ade; Thalo, Ota W.J.; Wae, Konsenius W. (Global Journal of Earth Science and Engineering, 2024)
The Flores back-arc thrust fissure is a significant contributor to earthquake events in the Flores Sea region, as evidenced by seismic investigations. As part of the endeavor to mitigate earthquake risk, seismic data investigations are necessary due to the high potential for earthquakes in the Flores Sea. Background noise in earthquakes is the term used to describe the micro vibrations that are perpetually produced as a result of natural phenomena, such as ocean waves, wind, or human activities. It is crucial to investigate this cacophony in seismology in order to distinguish the primary earthquake signal. Its spectrum analysis can assist in the identification of land changes and the prediction of tectonic activity. This analysis was conducted by employing the Incorporated Research Institutions for Seismology (IRIS) client function as a fetch data tool and the Modular Utility for Statistical Knowledge Gathering Data browser as a data quality monitoring system to verify the health and reliability of seismic data. The three station sites closest to the Flores Sea are the focus of this research data examination. The study's findings indicate that the recorded data at the station is still dominated by cultural noise, as evidenced by the analysis of the probability density function, power spectral density, and noise spectrograms. Additionally, each station exhibits activity with degrees of probability noise that are both high and variable. These results highlight the need for advanced techniques to filter cultural noise and improve the accuracy of seismic signal interpretation in this region. This analysis contributes to understanding tectonic activity in the Flores Sea and underscores the importance of continuous monitoring for earthquake preparedness and risk reduction.